FEMALE DEITIES IN THE RIGVEDA - Krishnamoorthy, K. (Journal of Dharma, 1980)
Writing in the ’Encyclopaedia of Religion and Ethics’, A. A. Macdonell remarks that’ Goddesses play an insignificant part in the Vedas, taking no share in the Government of the World.’ 1 Earlier, Max Muller, the doyen of Indologists, held the view that’ not all the Vedic female deities are purely abstract creations,’ since some of them have their physical prototypes such as Apas, the Waters, whether in the earth or in the sky, Usas, the Dawn, Prthivi, the Earth, Apsarases, the Water-nymphs, Sarasvati, the River, Aditi, the Beyond, and Prithvi, the Cloudy sky, the mother of the Maruth.